Virtual reality and sports performance: a systematic review of randomized controlled trials exploring balance - Cariati, Ida; Bonanni, Roberto; Cifelli, Pierangelo; D'Arcangelo, Giovanna; Padua, Elvira; Annino, Giuseppe; Tancredi, Virginia (Frontiers in Sports and Active Living, 2025)
IntroductionOur systematic literature review aimed to select randomized controlled trials (RCTs) in which virtual reality (VR) has been used in athletes or players to evaluate the effectiveness of this technology in gaining performance.MethodsIn accordance with PRISMA guidelines, a systematic literature search was conducted in the MEDLINE, Scopus and Web of Science databases using the keyword set [(Virtual reality) OR (VR)] AND [(Athletes) OR (Players)] AND [(Performance) OR (Balance)]. Peer-reviewed articles published within the last ten years in English and open access were included. The methodological quality of the articles was assessed using the Jadad scale, while the eligibility criteria were evaluated using the PICOS approach.ResultsSpecifically, six RCTs were selected, one of which scored 5/5 on the Jadad scale, four scored 3/5 and one scored 2/5. Importantly, five RCTs found a positive influence of VR on performance in terms of balance, stability, sprinting, jumping, neurocognitive function, reaction time and technical skills, while only one RCT found no difference in these parameters.DiscussionIn conclusion, the results included in our systematic review showed that VR seems to have a positive effect in improving sports performance. However, the heterogeneity of the studies did not allow for a comparison of the data to clarify the relevance of VR technology in performance, suggesting the need for in-depth investigations to confirm its efficacy in sports.